Victims’ testimony as pedagogical resource. Contributions for colombian post-conflict - Uribe, Julián Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article was developed on the basis of findings from Testimony as pedagogical category. A theoretical foundation, a current research conducted by its author in fulfillment of the requirements for the degree of PhD in education from the Universidad Autónoma de Barcelona. It is a qualitative study that falls within the hermeneutic approach, which uses documentary research as a method for presenting, from an analytical and critical perspective, some proposals regarding the pedagogical potential of victim’s testimony in post-conflict situations. This testimony was included in the Final agreement to end the armed conflict and build a stable and lasting peace, signed by the Colombian government and the FARC-EP, as a strategy oriented towards compensation of victims and reconciliation. For this purpose, the following subjects are previously addressed: testimony conceptualization, typology of testimony according to Ricoeur and assessment of its reception in the agreement.